A model for human settlement development and management in the Free State Province, South Africa - Dintsi, Sive; Mbanga, Sijekula; Smallwood, John (Frontiers in Sustainable Cities, 2025)
This paper aims to uncover the factors that influence the formulation of informal settlements upgrading programmes in the Free State Province of South Africa, from an institutional point of view. The paper subsequently yields a transformative and multi-faceted model for human settlement development and management from a combined institutional and systems theoretical perspective. The study is situated within the critical pragmatism knowledge paradigm, applying a mixed methods exploratory research design and inclined to research procedures that include the qualitative inductive content analysis method, case study method and the semi-structured survey questionnaire method. The sample selection is comprised of the non-probability sampling method, which is purposive and deliberate in nature. The data collection processes included document reviews, field observations and online surveys. The data analysis involved the abstraction and mapping of categories for the reviewed documents, descriptive analysis such as photos, written notes, and discussions with municipal officials for the field observations, and the software QuestionPro to analyze the collected data through online surveys. The research findings of the study revealed significant shortcomings related to policy design and implementation, stakeholder engagement practices, competencies of housing and human settlement practitioners, corrupt activities in the provision of adequate housing, disconnect in theory and practices during identification and definition of informal settlements, and the influence of illegal immigration on increasing housing need in South Africa. The study’s findings form the foundation of the proposed model in this paper. They may assist human settlement practitioners in both the public and private sectors in developing and managing sustainable human settlements in the forthcoming decades.